Deiksis Bahasa Dawan Dalam Peristiwa Sosial - Kaesmetan, Jurina; Djawa, Alex; Nitbani, Semuel H. (Jurnal Lazuardi, 2025)
This research is entitled Dawan Language Deixis in Social Events which is studied using the pragmatic theory proposed by Charles Moris (1938). Pragmatics is the science of pragmatics, namely the relationship between signs and their use. Pragmatics can be understood from various aspects, including: (1) the study of language in communication, especially the use of language (the relationship between language elements and context and situation); (2) the problem of interpretation (semantic) and the use of speech in reality; (3) the use and understanding of speech acts; (4) the influence of sentence structure because of the relationship between speaker and listener (greeter-greeter). With descriptive-qualitative methodology, the results of the study show that there is the use of social deixis in Dawan language with 48 types of existing social forms, such as; mu, pah, in, na ', bi, nadan others. The results of the study show that the social deixis used is in the form of words and phrases and has various functions such as; 1) as a medium to explain a person's social level; 2) to maintain politeness in language and others. In Dawan language, the meaning of social deixis is the meaning of a word or phrase whose referent moves or changes, depending on who says it, when, where, and depending on the context in communicating. Keywords: social deixis, pragmatics, form, function and meaning.